OPTIMALISASI PENGEMBANGAN “Setra Ari-Ari” SEBAGAI DAYA TARIK WISATA BUDAYA DI DESA BAYUNG GEDE, KECAMATAN KINTAMANI, KABUPATEN BANGLI - Fatrisia Yulianie; Kadek Feni Aryati; I Wayan Kiki Sanjaya (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
This article is about the optimalization of the development of “Setra Ari-Ari” As A Cultural Tourism Attraction in Bayung Gede Villages, Kintamani District, Bangli Regency. This article is aimed to find an effort that needs to be made to optimize the development of the Setra Ari-Ari cultural tourism attraction so that it can provide benefits to local communities without reducing the existing sacred and preservation values. Data were collected through observation, interviews, and documentations. The sampling techniques used were purposive sampling. Data were analyzed by using descriptive qualitative analysis to give an overview optimalization of the development of “Setra Ari-Ari” As A Cultural Tourism Attraction in Bayung Gede Villages, Kintamani District, Bangli Regency. The finding shows that Setra Ari-Ari has a unique culture that only Bayung Gede Village has, because of the tradition of hanging the placentas of newborns which are placed in coconut shells and hung on the Bukak tree (Cerbera manghas). There are efforts to develop the Bayung Gede Tourism Village including the Setra Ari-Ari. However, this effort is still not optimal in developing Setra Ari-Ari as a tourist attraction. The efforts that need to be made so that the development of the potential of Setra Ari-Ari can be more optimal, namely increasing tourism activities to make it more attractive, optimizing the use of tourism facilities and adding other facilities, increasing promotions and cooperation with other parties, improving the quality of human resources, and maintaining cleanliness. in the surrounding environment